PERANCANGAN MEDIA AUGMENTED REALITY DALAM PEMBELAJARAN MENGENAL HARDWARE DASAR PADA MULTIMEDIA - Nurrisma Nurrisma (TEKNIMEDIA: Teknologi Informasi dan Multimedia, 2025)
Digital transformation in vocational education demands innovative learning media capable of enhancing interactivity and students' self-directed learning motivation. This research developed an interactive learning media based on Augmented Reality for basic multimedia materials using the ADDIE model with Android platform, Unity, and Vuforia SDK. Research subjects involved media experts, material experts, and fifteen students of grade XI Graphic Design at SMK Negeri 1 Banda Aceh. Data collection was conducted through structured questionnaires with Likert scale, systematic observation, and semi-structured interviews. Validation results indicated very high feasibility percentages from media experts at 91.3%, material experts reaching 95%, and end-user evaluation showing 97.6% satisfaction. The developed learning media provided interactive features including three-dimensional object manipulation, multi-perspectival exploration, and contextual information access facilitating independent learning. Mobile-based Augmented Reality implementation offered learning flexibility unrestricted by space and time, enabling students to explore materials autonomously. Findings confirmed substantial potential of Augmented Reality technology in enhancing learning interactivity and self-directed learning motivation for basic multimedia materials in Indonesian vocational education context.